African traditional medicines-antiretroviral drug interactions: the effect of African potato (Hypoxis hemerocallidea) on the pharmacokinetics of efavirenz in humans - Mogatle, Seloi (Rhodes University, Faculty of Pharmacy, Pharmacy, 2009)
African Potato (Hypoxis hemerocallidea), (AP) is an African traditional medicine (TM) that is commonly used for various nutritional/medicinal purposes and also by people infected with the human immuno deficiency virus HIV and AIDS patients as an immune booster. The use of AP has also been recommended by the former Minister of Health of South Africa for use by HIV positive people. The main phytochemical component of AP is a norlignan glucoside, hypoxoside, and other relatively minor components have also been reported. A recent in vitro study reported the effects of AP extracts, hypoxoside and rooperol (the metabolite of hypoxoside) on human metabolic enzymes such as the cytochrome P450 (CYP450) group of enzymes and also on the transporter protein, p-glycoprotein (P-gp). This research focussed on investigating the clinical significance of those in vitro effects on the pharmacokinetics of efavirenz (EFV) in humans. EFV was chosen as the substrate drug because it is in first-line regimen of treatment of HIV/AIDS in South Africa, and also has been reported to be a substrate for the specific CYP isozymes, 3A4 and 2B6, in common with APs metabolic involvement with 3A4. A high performance liquid chromatography method with ultra-violet detection (HPLC-UV) for the quantitative determination of EFV in plasma was developed and successfully validated according to international standards with good reproducibility, accuracy, recovery, linear response and requisite sensitivity. The preparation of the plasma samples for analysis was effected by using a simple and rapid precipitation method, and the mobile phase consisted of readily available solvents. EFV in plasma samples was found to be stable under the relevant storage conditions studied. The oral dose of AP, administered as a freshly prepared traditional decoction, was standardised based on the hypoxoside content, and the quality of all the AP decoctions was analysed immediately prior to administration, using a validated HPLC-UV method. A single dose, two-phase sequential study was conducted over a period of 31 days in 10 healthy volunteers. The clinical study was approved by the Rhodes University Ethical Standards Committee, and all the participants agreed to the conditions of the study by giving their informed consent. On day 1 of the study, human subjects were administered a 600 mg EFV tablet and blood samples were collected before dosing and at various intervals over a period of 48 hr post dosing. From day 16, a traditionally prepared AP decoction was administered daily at a standardized dose of 15 mg/kg/day per subject until day 30. On day 29, volunteers were administered a single 600 mg dose of EFV as was done on day 1. Plasma samples were harvested immediately after blood sample collection and frozen at -80 ÂºC until assayed. Geometric mean ratios of relevant pharmacokinetic parameters, Cmax (maximum plasma concentration achieved following dosing) and AUC0-48 (area under the curve of a plot of drug plasma concentrations versus time representing the extent of absorption) of EFV before and after co-administration of 14 successive daily doses of AP were compared and evaluated to determine whether an interaction had occurred. All subjects completed the study and the geometric mean ratios of Cmax and AUC0-48 were 97.30 and 102.82 with corresponding 90% confidence intervals (CIs) of 78.81-120.14% and 89.04-118.80%, respectively. Whereas the acceptance criteria for the ratios of the AUCs fell within the preset 90% CIs indicating no interaction, the Cmax ratios fell outside the limits. Although the protocol was developed in accordance with the United States of America Food & Drug Administration's Guidance for Drug Interactions, a priori stating that both criteria need to fall within the acceptance limits to indicate no interaction, an argument is presented to waive the Cmax requirement for the declaration of an interaction. As a result, the pharmacokinetic data generated during this study indicated that the effect of AP on the pharmacokinetics of EFV is not clinically significant. Hence, co-administration of AP is unlikely to affect the clinical use of EFV. In summary the objectives of this project were: 1. To develop and validate a suitable HPLC-UV method for the quantitative determination of EFV in plasma. 2. To perform a mini-validation of the determination of hypoxoside for use as a marker in the quality control and standardisation of AP decoctions. 3. To conduct a clinical interaction study in order to determine whether AP affects the pharmacokinetics of EFV following concurrent administration. 4. To apply the validated HPLC-UV method to determine plasma concentrations of EFV in plasma of human subjects. 5. To use appropriate statistical methods and treatments such as a non-compartmental pharmacokinetic analysis to determine the occurrence of an interaction.
Keywords: Potatoes -- Africa; Potatoes -- Therapeutic use; Medicinal plants; Traditional medicine; AIDS (Disease) -- Treatment; HIV infections -- Drug therapy; Drug interactions; Antiretroviral agents; Pharmacokinetics; Hypoxidaceae -- Therapeutic use; High performance liquid chromatography